Prevalensi dan karakteristik supernumerary teeth pada anak usia 13-15 tahun di Makassar (The prevalence and characteristics of supernumerary teeth for children of 13-15 years old in Makassar) - Asmawati Asmawati; Bahruddin Thalib; Nurul Mutmainnah (DiscoverSys Inc., 2014)
Supernumerary teeth is an abnormality in the form of increasing amount of teeth more than the normal amount, thatis more than twenty twenty in the decidui dentition or thirty two in the permanent dentition. The objective of thepresent study was to investigate the prevalence and characteristics of supernumerary teeth of 13-15 year old childrenin Makassar. This descriptive study involved 13-15 year old children who were present during the oral examinationin 14 junior high schools in Makassar. This cross-sectional study employed random sampling method. This studyfound 24 supernumerary teeth which yield a prevalence of 0.6%. The prevalence among male was higher thanamong female (M:F of 2.1:1). The greatest proportion of supernumerary teeth was found in the maxillary anteriorregion consisting of single supernumerary teeth (90.9%)and multiple supernumerary (9.1%). The prevalence ofcharacteristic sample based on their site of supernumerary teeth is mesiodens (58.3%) and lateral incisor (41.7%).Out of the 24 supernumerary teeth, 93.8% erupted and 4.2% partial erupted. The prevalence of characteristic samplebased on their morphology is conical (83.4%), tubercular (8.3%), and supplementale (8.3%). This study concludedthat the prevalence of supernumerary teeth for children of 13-15 years old in Makassar was found higher among male(ratio M:F of 2.1:1)and they are most frequently located in the maxilla. Most cases presented only single supernumeraryand in multiple cases the mesiodens region is predominant, with the conical shape is the commonest morphology.